THE USE OF NUMBERED HEAD TOGETHER (NHT) TO INCREASE STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT AT SMP NEGERI 1 LANGOWAN - Feiby Sekeon; Paula Hampp; Sarah Kamagi (Program Studi Pendidikan Bahasa Inggris, 2022)
The purpose of this research is to find out whether Numbered Head Together Techique is effective to increase students’ reading comprehension especialy in narrative text. In terms of purpose Based on explanation above, the writer wants to apply Numbered Head Together (NHT) in increasing students’ reading comprehension especially on narrative text. The writer hopes by using Numbered Head Together (NHT) for teaching reading can help students get an improvement in reading especially in narrative text. The result of this research shows that the score of the students in post-test are higher than the students’ score in pre-test. The mean score of pre-test was 48,03 while the mean score of post-test was 74,82. It was clear that the result of post-test was better than pre-test. Using narrative text (fable) in teaching reading helped students to improve their reading ability in comprehend the written text, especially narrative text. Since the use of fable is effective to overcoming students’ problem in comprehending reading text, English teachers are suggested to apply narrative text (fable) in teaching reading narrative text in order to make the teaching learning process more effective and enjoyable. The teacher should provide interesting materials, in order to prevent the students from being bored.